2019
DOI: 10.3171/2017.9.jns171806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of choice of treatment modality on the incidence of shunt-dependent hydrocephalus after aneurysmal subarachnoid hemorrhage

Abstract: OBJECTIVE Shunt-dependent hydrocephalus (SDHC) may arise after aneurysmal subarachnoid hemorrhage (aSAH) as CSF resorptive mechanisms are disrupted. Using propensity score analysis, the authors aimed to investigate which treatment modality, surgical clipping or endovascular treatment, is superior in reducing rates of SDHC after aSAH. METHODS The authors' multicenter SAH database, comprising 3 stroke centers affiliated with Kyoto University, Japan, was used to identify patients treated between January 2009 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Some studies have suggested that endovascular treatment is independently associated with the development of chronic hydrocephalus in aSAH patients [ 124 , 125 ]. However, other research has demonstrated a significantly lower incidence of chronic hydrocephalus after endovascular treatment compared with after surgical clipping [ 126 ]. Surgical clipping via the traditional pterional transsylvian approach with arachnoid membrane dissection may directly alter CSF flow dynamics and resorption [ 126 ].…”
Section: Coil Vs Clip and Their Relationship With Shunt Dependencymentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have suggested that endovascular treatment is independently associated with the development of chronic hydrocephalus in aSAH patients [ 124 , 125 ]. However, other research has demonstrated a significantly lower incidence of chronic hydrocephalus after endovascular treatment compared with after surgical clipping [ 126 ]. Surgical clipping via the traditional pterional transsylvian approach with arachnoid membrane dissection may directly alter CSF flow dynamics and resorption [ 126 ].…”
Section: Coil Vs Clip and Their Relationship With Shunt Dependencymentioning
confidence: 99%
“…However, other research has demonstrated a significantly lower incidence of chronic hydrocephalus after endovascular treatment compared with after surgical clipping [ 126 ]. Surgical clipping via the traditional pterional transsylvian approach with arachnoid membrane dissection may directly alter CSF flow dynamics and resorption [ 126 ]. In a retrospective review of 839 patients with aSAH [ 127 ], endovascular coiling was associated with a lower risk of shunt dependency for Fisher grade 2 patients (2% vs. 13% with clipping, p = 0.043), while surgical clipping lowered the likelihood of shunt dependency in patients with Fisher grade 4 aSAH (23% vs. 44%, p = 0.004).…”
Section: Coil Vs Clip and Their Relationship With Shunt Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…The overall methodological quality of cohort studies included was relatively high, as 70.00% of them earned ≥ 8 scores. The representativeness of the cohort was low in 5 studies because they did not include consecutive or random samples [2,16,28,52,60]. Seven studies did not state clearly how they assessed the outcomes [3,12,16,25,46,56,60].…”
Section: The Methodological Quality Of the Included Studiesmentioning
confidence: 99%
“…The rate of development of chronic hydrocephalus after aSAH was affected by treatment modality used to secure the ruptured aneurysm, whether microsurgical clipping or endovascular coiling, in some reports and not affected in other ones. [ 1 , 2 , 9 , 11 , 13 , 15 - 19 , 23 , 29 , 30 , 32 , 33 , 46 , 47 , 49 ]…”
Section: Introductionmentioning
confidence: 99%